Preoperative Anxiety and Its Associated Factors in Patients Undergoing Cardiac Catheterization: A Meta-Analysis - Atmojo, Joko Tri; Awaludin, Sidik; Kamalludin, Ridlwan (Universitas Muhammadiyah Surakarta, 2026)
Preoperative anxiety is a common psychological response among patients undergoing invasive procedures such as cardiac catheterization and may adversely affect hemodynamic stability and procedural outcomes. Evidence regarding factors associated with preoperative anxiety remains inconsistent. This study aimed to estimate the magnitude of associations between selected factors and preoperative anxiety in patients undergoing cardiac catheterization.A meta-analysis was conducted using articles retrieved from PubMed, Google Scholar, and ScienceDirect, published between 2015 and 2025. Study selection followed the PICO framework: patients undergoing cardiac catheterization; exposure factors included female gender, high social support, history of surgery, and educational status; and the outcome was preoperative anxiety. Only full-text cross-sectional studies were included. Data were analyzed using Review Manager (RevMan) version 5.3. Fourteen studies from Palestine, Nepal, Malaysia, Vietnam, Finland, Italy, Spain, Greece, Iran, Ethiopia, Canada, and China were included. The meta-analysis showed that female gender (aOR = 0.54; 95% CI: 0.37–0.80; p = 0.002), high social support (aOR = 0.64; 95% CI: 0.49–0.84; p = 0.001), and a history of surgery (aOR = 0.60; 95% CI: 0.39–0.90; p = 0.01) were protective factors against preoperative anxiety. In contrast, being educated was associated with a higher risk of preoperative anxiety (aOR = 1.64; 95% CI: 1.25–2.15; p = 0.0004). In conclusion, female gender, strong social support, and previous surgical experience reduce preoperative anxiety, whereas higher educational level increases anxiety among patients undergoing cardiac catheterization.